Innovation of Hybrid Solar and Gas-Powered Maggot Dryer Machine as a Solution for Dry Feed - Pinandita, Satria; Jayati, Ari Endang; Derman, Derman; Elawati, Nunung Eni; Ramadan, Bimastyaji Surya (Journal of Community Empowerment, 2025)
Sugihmanik Village, a major tofu production center, produces substantial amounts of organic waste, particularly wastewater that contaminates local rivers and disrupts the surrounding ecosystem. A community service program has been developed to convert tofu waste sludge into maggot feed, followed by drying using a hybrid solar and gas-powered maggot drying machine. Initial activities involved program outreach and technical training on maggot cultivation and the drying process. A drying trial demonstrated that 200 grams of wet maggots were reduced to 114 grams within seven minutes. Monthly drying operations required only four 3-kg LPG cylinders, resulting in 81 kilograms of dry maggots and a potential monthly income of IDR 4.050.000. Environmental degradation caused by tofu waste has been significantly mitigated, while local economic productivity has improved. The drying machine enhances the commercial value of maggots as durable livestock feed. The initiative strengthens the operational sustainability of the Krida Manik Waste Bank and offers a scalable model for resource-based environmental solutions.